2018
DOI: 10.1017/jfm.2018.664
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional instability of a flow past a sphere: Mach evolution of the regular and Hopf bifurcations

Abstract: A fully three-dimensional linear stability analysis is carried out to investigate the unstable bifurcations of a compressible viscous fluid past a sphere. A time-stepper technique is used to compute both equilibrium states and leading eigenmodes. In agreement with previous studies, the numerical results reveal a regular bifurcation under the action of a steady mode and a supercritical Hopf bifurcation that causes the onset of unsteadiness but also illustrate the limitations of previous linear approaches, based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 50 publications
7
34
0
Order By: Relevance
“…Figure 3 shows the distribution of the flow regime in the Re-M plane under compressible conditions. The results of the previous studies by Nagata et al (2016), Riahi et al (2018) and Sansica et al (2018) are shown for comparison with those of the present study. The result of Nagata et al (2016) is obtained by the three-dimensional DNS with a boundary-fitted coordinate (BFC) grid, the result of Riahi et al (2018) is obtained the three-dimensional DNS with IBM, and the result of Sansica et al (2018) is obtained the three-dimensional GSA, respectively.…”
Section: Flow Regimesupporting
confidence: 69%
See 2 more Smart Citations
“…Figure 3 shows the distribution of the flow regime in the Re-M plane under compressible conditions. The results of the previous studies by Nagata et al (2016), Riahi et al (2018) and Sansica et al (2018) are shown for comparison with those of the present study. The result of Nagata et al (2016) is obtained by the three-dimensional DNS with a boundary-fitted coordinate (BFC) grid, the result of Riahi et al (2018) is obtained the three-dimensional DNS with IBM, and the result of Sansica et al (2018) is obtained the three-dimensional GSA, respectively.…”
Section: Flow Regimesupporting
confidence: 69%
“…The flow past a sphere under the compressible low-Re flow has numerically been studied by Nagata et al (2016), Riahi et al (2018) and Sansica et al (2018). Nagata et al (2016Nagata et al ( , 2018a used DNS with a body-fitted grid to investigate fundamental characteristics such as aerodynamic force coefficients, flow structures and flow regime, with a stationary adiabatic sphere at 0.3 ≤ M ≤ 2.0 and 50 ≤ Re ≤ 300.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile the real parts of the conjugate eigenvalues increase above zero and STLE instability occurs. The evolution of the conjugate eigenvalues also indicates the occurrence of a Hopf bifurcation ( Sipp et al 2010;Sansica et al 2018). When C f decreases further, the real parts of the conjugate eigenvalues separate at some positions and the imaginary parts disappear.…”
Section: Linear Stability Analysis Of the Shock Train Movementmentioning
confidence: 99%
“…2010; Sansica et al. 2018). When decreases further, the real parts of the conjugate eigenvalues separate at some positions and the imaginary parts disappear.…”
Section: Mechanism Of the Unsteady Movement Induced By Swblimentioning
confidence: 99%